PENGARUH RASIO LIKUIDITAS DAN PROFITABILITAS TERHADAP PENERIMAAN OPINI AUDIT GOING CONCERN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2009-2013 - Hj. Dewi Rejeki, SE., Ak., M.Ak.; Erwina Syahputra T (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2015)
Abstract : The reason this study of course, there is a problem regarding the acceptance of dysfungtional audit behavior in the audit process that does not comply with audit procedures that have been established or deviate from the applicable standards, so as to reduce the quality of the financial statements being audited. Based on cluster sampling method with stratified random sampling technique, this study used a sample amount to 15 KAP with a total of 98 respondents who work as auditors working in the public accounting firm located in South Jakarta enrolled in AP & Firm Directory 2014 publish by IAPI. This study uses primary data by questionnaire. Data were analyzed using multiple regression analysis processing through SPSS 22,0 statistical software. The results showed two variables that have an influence ang significant to the Audit Dysfungtional Behavior namely external locus of control variables and performance while variable organizational commitment and turnover intention has significant influence but not on accepteance of dysfungtional audit behavior. The conclusion of this study, shows that of the four variables tested partially to irregularities in the conduct of the audit, only two variables that have an influence and significant to the Audit Dysfungtional Behavior namely external locus of control variables and performance while variable organizational commitment and turnover intention has influence but not significantly to the acceptance of dysfungtional audit behavior. Suggestions from this study, expected to examine other factors that affect the practice of auditing dysfunctional behavior such as : job satisfaction, controlling system, underreporting of time and time pressure. In addition, this study is expected to provide remedial measures against those aspects that can trigger an audit dysfungtional behavior practices that audit quality in maintained.